Self, text, and romantic irony : the example of Byron - Garber, Frederick (Princeton legacy library., 1988)
Frederick Garber takes up in detail several problems of the self broached in his previous book, The Autonomy of the Self from Richardson to Huysmans (Princeton, 1982). Using patterns in Byron's canon as models, he focuses on the relations of self-making and text-making as a central Romantic issue. For Byron and many of his contemporaries, putting a text into the world meant putting a self there along with it, and it also meant that the difficulties of establishing the one inevitably reflect the parallel difficulties in the other. Professor Garber discusses some of Byron's key texts and shows how their development leads to an impasse involving both self and text. Byron's way out of these dilemmas was the mode of Romantic irony, of which he is one of the greatest exemplars. The study then moves into broader areas of Anglo-European literature, its ultimate purpose being to argue not only for the efficacy of such irony but for its position as something more than a mere alternative to Romantic organicism. Originally published in 1988. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.